Attosecond delays in photoionization of diatomic and polyatomic molecules. Issue 7 (January 2020) - Loriot, V; Marciniak, A; Nandi, S; Hervé, M; Karras, G.; Constant, E; Lépine, F
Synopsis: We have investigated the photoionization dynamics of several molecular systems using attosecond in-terferometric techniques based on ultrashort extreme ultraviolet (XUV) pulses. For diatomic molecules such as N2, we can get a detailed picture of the photoionization process by measuring the attosecond delays. For polyatomic molecules such as naphthalene, such measurements can provide the average timescale over which photoionization processes at different electron energies can occur in complex quantum systems.